Gender Manipulation and Comic Identity in Roman Comedy - Tran, Cassandra (My University, 2023)
Roman Comedy is defined by the tensions between comic convention and humour’s ability to interrogate societal norms. The playwrights, Plautus and Terence, experimented with their generic restrictions to create unique and complexly structured plays that posed questions on personal and collective identity. This study identifies a critical framework of gender manipulation that shows how citizen men of comic plays transgressed traditional norms of masculinity on a relational, physical, and structural level. It is grounded on the idea that gender plays an integral role in constructing the self. Once characters transgress their gender, other aspects of their identity adjust accordingly until they assume a new social and comic role. I divide my analysis into three character studies from Plautus’ Menaechmi, Terence’s Eunuchus, and Plautus’ Casina. I argue that both playwrights follow the same pattern, where a citizen man performs a physical act of gender transgression in response to dissatisfaction with his emasculating relationship with a female counterpart. This act reveals tensions pertaining to cultural dissonance and citizenship, sexuality in the transition to adulthood, and the crisis of old age. It is followed by a structural manipulation that shifts character and narrative tropes to bring the play to some resolution. This study provides a new framework for investigating the relationship between character and narrative, as well as generic convention and comic subversion in Roman Comedy. It diverges from recent scholarship on comic gender roles to reveal the distinct ways that Plautus and Terence experimented with the patriarchal constructions of masculinity and femininity in addition to the binarism of gender.
Keywords: Roman Comedy; Gender and sexuality; Queer theory; Gender theory; Latin literature; Comedy and performance